2012
DOI: 10.1590/s0100-06832012000400012
|View full text |Cite
|
Sign up to set email alerts
|

Organic matter quality and dynamics in tropical soils amended with sugar industry residue

Abstract: SUMMARYSoil organic matter depletion caused by agricultural management systems have been identified as a critical problem in most tropical soils. The application of organic residues from agro-industrial activities can ameliorate this problem by increasing soil organic matter quality and quantity. Humic substances play an important role in soil conservation but the dynamics of their transformations is still poorly understood. This study evaluated the effect of compost application to two contrasting tropical soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…All values referring to SBR and qCO 2 suggested that microbial populations operate in the absence of metabolic stress (Silva et al, 2014). We know that organic matter from SS when applied to soils of tropical regions is rapidly degraded (Busato et al, 2012;Vieira et al, 2014 and the increase of organic matter in the soil over time is very low or zero (Yada et al, 2015, Kirchmann et al, 2017. In the present study, no increase of soil organic matter was observed due to the addition of SS in the first ten years of the experiment (Table 2).…”
Section: Discussionsupporting
confidence: 42%
“…All values referring to SBR and qCO 2 suggested that microbial populations operate in the absence of metabolic stress (Silva et al, 2014). We know that organic matter from SS when applied to soils of tropical regions is rapidly degraded (Busato et al, 2012;Vieira et al, 2014 and the increase of organic matter in the soil over time is very low or zero (Yada et al, 2015, Kirchmann et al, 2017. In the present study, no increase of soil organic matter was observed due to the addition of SS in the first ten years of the experiment (Table 2).…”
Section: Discussionsupporting
confidence: 42%
“…Compost presented CEC of 119.0 cmol c kg -1 (Table 1) and, similarly to EC, there is not a reference value for CEC in Brazilian regulations. The CEC in the compost is due to the presence of carboxyl, carbonyl, phenolic hydroxyl, ether and hydroxyl present in the compost (Busato et al, 2012). The observed value for CEC in the compost is higher when compared with the natural CEC in the soils from the Cerrado biome (Lopes & Guilherme, 2016).…”
Section: Chemical Characterization and E Coli Testmentioning
confidence: 88%
“…Compost application in the soil increases organic matter and improves soil productivity, since this component is the ultimate source of nutrients and microbial activity. The soil organic carbon preservation after compost addition depends on soil mineralogy (Busato et al, 2012). According to these authors, in weathered soils, some organic fractions, such as fulvic acids, are strongly sorbed by oxides due to their large amounts of carboxylic groups, increasing the residence time of these materials in the soil.…”
Section: /9mentioning
confidence: 99%
“…The pH reduction results from the addition or retention of organic matter, with organic acid produced from decomposition of plantderived materials. The decomposition of organic matter results in the formation of both organic and inorganic acids (Busato et al, 2012), which cause the basic ingredients of the potting medium, such as calcium, to dissolve and eventually leach out, resulting in lowered medium pH. However, other researchers (Watson and Kupkowski 1991;Greenly and Rakow, 1995) found no change in soil and media pH after applying organic mulches.…”
Section: Discussionmentioning
confidence: 99%